Dynamic response of beams excited by moving oscillators: Approximate analytical solutions for general boundary conditions. (May 2023) - Di Matteo, Alberto
Highlights: Beams with general boundary conditions subjected to moving oscillators with damping. Approximate closed-form solutions for both beam and moving oscillator displacements. Solution derived through an expansion approach for small oscillator-beam mass ratio. Simple analytical expressions explicitly depend on the coefficient of the polynomials. Straightforward application of the solutions for any boundary condition. Abstract: In this paper, the dynamic response of an Euler-Bernoulli beam with general boundary conditions (BCs) and subject to a moving oscillator is examined. Notably, novel approximate closed-form expressions are determined for the vertical responses of both the beam and the moving oscillator, specifically considering the effect of damping in these systems, commonly omitted in standard approaches in the literature. In this regard, a modal superposition procedure is adopted and combined with an appropriate expansion-based approach of the dynamic response of the system, which naturally arises considering the oscillator-beam mass ratio to be reasonably small. Further, general boundary conditions are treated exploiting the use of a suitable set of orthogonal polynomial functions as beam mode shapes. In this manner, novel direct expressions for the response of the system are derived, in which the mode shapes coefficients explicitly appear. This leads to a straightforward application of the proposed solution, irrespective of the chosen BCs. Several numerical examples are presented to assess the reliability and accuracy of the proposed approach, considering different cases of beam BCs, and moving oscillator's parameters. Results are validated by comparison with the data of finite element analyses, and numerical solutions of the complete system of governing equations.